Runtuhnya Pilar Demokrasi Akibatkan Politik Dinasti: Menelisik Jejak Hitam Nepotisme Anwar Usman - Devi, Murtanti Fajarrani; Putri, Salsabila Restia; Syahir, Fabhian Halky; Raharjo, Angga Sandhika; Asmara, Daffi Allegra; Latri, Akhdan Adityo; Delyananda, Zahrah Rani’ah; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
The phenomenon of dynastic politics in Indonesia has become a major highlight in contemporary democratic discourse, especially when the involvement of families of public officials extends into the realm of judicial power. One case that has generated great controversy is the Constitutional Court Decision Number 90/PUU-XXI/2023, which paved the way for Gibran Rakabuming Raka the son of President Joko Widodo to run in a national political contest. The decision was colored by a conflict of interest following the involvement of the Chief Justice of the Constitutional Court, Anwar Usman, who has a direct kinship with the party benefiting from the decision. This situation raises serious questions about the integrity of the judiciary, the neutrality of judges, and the effectiveness of the legal profession's code of ethics in safeguarding democratic principles and the rule of law. Using a normative juridical approach and a case approach, this analysis focuses on relevant legislation and court decisions, to unravel the extent to which Indonesia's legal mechanisms are able to prevent and crack down on the practice of nepotism in constitutional institutions. Violation of the principle of nemo judex in causa sua (not to hear cases involving personal interests) is the main highlight in seeing the fragility of the pillars of democracy due to the dominance of family interests and patronage politics. In this context, strengthening the code of ethics, the role of the Honorary Council of the Constitutional Court, and revitalizing the basic principles of justice such as independence, impartiality and accountability are absolute prerequisites in maintaining public confidence in the constitutional justice system in Indonesia.